Uji Kualitas Kimia Kefir Dari Imbangan Susu Kambing Dan Susu Sapi Dengan Lama Fermentasi Yang Berbeda - Alfath Rusdhi; Purwo Siswoyo; Tiara Adelia (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
The research aims to study the quality of kefir chemistry from the balance of goat's milk and cow's milk with different fermentation periods. Research uses experimental methods with a complete random design of factorial patterns. The first factor is the type of milk (cow milk 100%, goat milk 50% + milk cow 50%, and goat milk 100%), the second factor is long permentation (24, 36 and 48 hours). The results showed the type of milk, the length of the permentation and the interaction of real effect on protein levels, fats, alcohol, total dissolved solids and total lactic acid. Kefir quality is a balanced high protein, low in fat and alcohol found in goat's milk kefir with fermentation for 60 hours, where the amount of protein is 4.16%, fat 4.27%, and alcohol 0.59%, Total dissolved solids 5.5667% and Total lactic acid is 0.7871%.